Pendampingan Kegiatan Kompetisi Polytechnic Creative Festival (PC FEST) pada Tahun 2024 Kategori Lomba Campus Website - M Arief Rahman; Amir Yusuf Arbain; Ade Dwi Prayoga (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The PC FEST 2024 Campus Website Competition successfully combined competitive and educational elements in order to enhance students' skills and creativity in web design and development. With wide participation from various universities in Indonesia, this competition highlighted the importance of responsive, informative, and interactive websites as digital representations of educational institutions. Through a series of intensive workshops, seminars, and mentoring sessions, participants were trained in the technical and aesthetic aspects of website creation, including coding, SEO, and multimedia integration. The competition focused on the practical application of the theory learned, with teams competing to create websites that were not only visually appealing but also functional and user-friendly. Evaluations from judges who are experts in the fields of information technology and web design provided valuable feedback for participants, allowing them to hone and refine their work further. The results of the competition showed significant progress in participants' skills and opened new insights into the potential use of digital technology in education. The competition not only showcased students' creativity and innovation, but also encouraged continued growth and development in the field of educational technology.